2018
DOI: 10.1017/jfm.2018.325
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse particle-laden exchange flows in a vertical duct

Abstract: We study buoyancy-driven exchange flow of two mixtures in a vertical narrow duct (two-dimensional channel as well as pipe) theoretically. While the light mixture is assumed always to be a pure fluid, the heavy mixture can be selected as either a pure or a particle-laden fluid. A small width-to-length ratio considered for the duct ($\unicode[STIX]{x1D6FF}\ll 1$) has been used as the perturbation parameter in developing a lubrication model (negligible inertia). In particular, we have adopted the methodology of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…The motion of elongated drops in vertical pipes arises in many engineering systems, such as buoyancy-driven displacements in wells and chemical reactors (Baird et al 1992;Frigaard & Scherzer 1998;Sahu & Vanka 2011;Alba, Taghavi & Frigaard 2014;Hasnain, Segura & Alba 2017;Etrati & Frigaard 2018;Mirzaeian & Alba 2018;Amiri et al 2019;Oladosu et al 2019). In nature, it is important for understanding conduit At timet = 0, the top part of the pipe is filled with the heavier, descending fluid (dark blue) and the bottom part with the lighter, ascending fluid (white).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion of elongated drops in vertical pipes arises in many engineering systems, such as buoyancy-driven displacements in wells and chemical reactors (Baird et al 1992;Frigaard & Scherzer 1998;Sahu & Vanka 2011;Alba, Taghavi & Frigaard 2014;Hasnain, Segura & Alba 2017;Etrati & Frigaard 2018;Mirzaeian & Alba 2018;Amiri et al 2019;Oladosu et al 2019). In nature, it is important for understanding conduit At timet = 0, the top part of the pipe is filled with the heavier, descending fluid (dark blue) and the bottom part with the lighter, ascending fluid (white).…”
Section: Introductionmentioning
confidence: 99%
“…The motion of elongated drops in vertical pipes arises in many engineering systems, such as buoyancy-driven displacements in wells and chemical reactors (Baird et al. 1992; Frigaard & Scherzer 1998; Sahu & Vanka 2011; Alba, Taghavi & Frigaard 2014; Hasnain & Alba 2017; Hasnain, Segura & Alba 2017; Etrati & Frigaard 2018; Mirzaeian & Alba 2018; Amiri et al. 2019; Oladosu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement interpenetration speed of the heavy and light phases are further quantified in these studies. Note that non-colloidal particle-laden flows within confined (duct) geometries studied by Mirzaeian & Alba (2018 a ) and Mirzaeian et al. (2020), furthermore, exhibit distinct behaviour compared to their free-surface flow counterparts examined by Zhou et al.…”
Section: Introductionmentioning
confidence: 91%
“…The use of a fish tank may reduce refraction errors associated with the curvature of the pipe [18,19]. While it is possible that the reported profiles of interface and displaced residual fluid layer slightly change via the use of a fish tank, recent benchmarking studies have shown that refraction errors do not affect bulk behavior of the flow and most importantly the displacing front velocity [15,20,21].…”
Section: A Apparatus and Measurementmentioning
confidence: 99%